The chocolate castle clue : a chocoholic mystery - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2011)
After Lee McKinney goes rummaging in a locked file cabinet, a 45-year-old cold case starts to heat up the town of Warner Pier. When Lee discovers a dusty trophy hidden away inside TenHuis Chocolade, she is eager to share it with her aunt Nettie. The timing couldn<U+2019>t be better - Nettie is hosting a reunion for her old high school singing group, the Pier-O-Ettes. Unfortunately, the trophy brings back terrible memories of the night of the group<U+2019>s trophy-winning performance at the Castle Ballroom. The ballroom<U+2019>s owner was found shot to death. The insurance company called it suicide; his wife insisted it must have been an accident; the town whispered, Murder. Now Lee has a mystery to solve. Before she can take aim at the events of the past, someone turns up murdered in the here and now. Lee needs to keep her eye on the prize and hope the trophy will be the clue to finding the killer - before she ends up as a target herself...